2015
DOI: 10.1590/s0004-28032015000400008
|View full text |Cite
|
Sign up to set email alerts
|

Human Dna Quantification in the Stools of Patients With Colorectal Cancer

Abstract: -Background -Colorectal cancer is one of the main cause of cancer in the world. Colonoscopy is the best screen method, however the compliance is less than 50%. Quantification of human DNA (hDNA) in the feces may be a possible screen non-invasive method that is a consequence of the high proliferation and exfoliation of cancer cells. Objective -To quantify the human DNA in the stools of patients with colorectal cancer or polyps. Methods -Fifty patients with CRC, 26 polyps and 53 with normal colonoscopy were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
(34 reference statements)
1
3
0
1
Order By: Relevance
“…In cancer patients due to exfoliation of tumor cells average human DNA content (15.05±30.7 ng/ul) was approximately 33 times higher when compared to the control group. Similar results have already been published by our group (Teixeira et al, 2015). Among patients with polyps, no differences were observed when compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In cancer patients due to exfoliation of tumor cells average human DNA content (15.05±30.7 ng/ul) was approximately 33 times higher when compared to the control group. Similar results have already been published by our group (Teixeira et al, 2015). Among patients with polyps, no differences were observed when compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…One interesting link here is provided by recently published results implicating inflammation-induced ETosis in extracellular matrix remodelling and awakening of dormant cancer cells[237]. As tumour-associated inflammation is a characteristic feature of CRC, and significantly increased extracellular trap formation in these tumours is now proven[238,239], it looks probable that previous reports of CRC-associated increase in the amount of DNA in stool[240,241] or on the surface of colorectal mucosa[190,242] at least partially reflected abundant ETosis occurring within mucus layers contacting tumour surface. In essence, cellular presence in the mucus overlaying colorectal tumour surface is quite similar to that depicted by Figure 3, the abundance of exfoliated malignant cells being the only major difference[190].…”
Section: Eosinophil Impact In the Pathogenesis Of Major Colorectal DImentioning
confidence: 86%
“…In other studies, risk factors including black race and a history of cancer or diabetes were closely related to RCC, while factors including white race, smoking, and high alcohol intake were closely associated with both LCC and ReC[1519]. Recent studies indicated that LCC had higher concentrations of human DNA in the stools than RCC[20], while RCC showed significantly higher mRNA expression levels of glycolysis genes than LCC[21]. Differences were also observed between proximal and distal colon cancers in common alterations of mucosal gene-expression profiles in CRC-associated microbiota [22].…”
Section: Discussionmentioning
confidence: 99%